Manajemen Kurikulum Muatan Lokal Berbasis Religius Sebagai Upaya Membentuk Karakter Islami Siswa - Nurhayati Iin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Management is a process of planning, implementation and evaluation compiled by a groupor individual in order to achieve a common goal. Religious-based local content curriculumis curricular and extracurricular activities to develop competencies that are tailored to thecharacteristics and potential of the region, including regional advantages, whose materialcannot be grouped into existing subjects. This type of research is qualitative, namelyresearch that intends to understand the phenomenon of what is experienced by theresearch subject such as behavior, perception, motivation, action, presented by way ofdescription in the form of words and language, in a special context that is natural and byutilizing various scientific methods. Data collection techniques in this study are byconducting observations, interviews and field notes.The steps in analyzing the data aredata reduction, data presentation, and drawing conclusions. The results of this studyindicate that the religious-based local content curriculum has an effect on the characterand development of students.